Chain-mediated effects of career self-efficacy and career planning between social support and career anxiety in college soccer players - Feng, Yu-Juan; Zhang, Zhen-Yu; Wang, Wei; Zhang, Wen-Juan; Che, Guang-Wei (Frontiers in Psychology, 2025)
The purpose of this study was to investigate the factors affecting the Career Anxiety of Chinese university high-level soccer players, to construct a chain mediation model, and to provide intervention suggestions to alleviate the Career Anxiety of this group. The study used questionnaires and collected 797 valid questionnaires (404 male; 393 female), and used AMOS 21.0 and SPSS 19.0 software for data processing and model testing through hierarchical regression and structural equation modeling. The results showed that: social support had a direct negative effect on Career Anxiety; career choice self-efficacy and career planning mediated between social support and Career Anxiety, respectively; and career choice self-efficacy and career planning together constituted a significant chain mediation effect. The conclusion suggests that improving the social support level, enhancing their career choice self-efficacy and perfecting their career planning ability are the key ways to effectively intervene in Career Anxiety among college high-level soccer players.